Pengaruh Atribut Produk Tabungan Terhadap Loyalitas Nasabah (Studi pada Bank XYZ KCP Antapani Bandung) - Limbong, Novi Septiani; Solihat, Ani (LPPM Universitas BSI, 2013)
ABSTRACT -Â Bank XYZ KCP Antapani Bandung from 2010 through 2012 had climbed down the number of customers . In 2010 the number of customers of Bank XYZ totaled 794 people , in 2011 dropped to 727 people , and in 2012 had increased back up to 844 people . The rise and fall of the number of clients showing low levels of customer loyalty in the bank . Customer loyalty will form one of the products offered . Product attributes are product elements that are considered important in the purchase decision .The purpose of this study is to determine how much product attributes that exist in Bank XYZ KCP Antapani Bandung affect the level of client loyalty .This research method using descriptive and verification object of study is the effect of variable X ( product attributes ) to Y ( customer loyalty ) were studied . The data of the research was obtained by observing spreading out the questionnairewith Likert scale and used descriptive and verificative method. Wherever,regressionequationobtainedis Y = 2,660 + 0,171X.Additionallyhypothesisresultsshowsavingsproduct attributevariableshavea positiveand significantimpacton customer loyalty. This is indicated by the results of the test score correlation and regression test and t-test reject Ho. Positive and significant influence does it mean if a product attribute factors include product quality, product features, product design, brand, warranty, price, increasing the quality of it will be followed by an increase in customer loyalty. Keyword : product attributes, customer loyalty.